2015
DOI: 10.1016/j.celrep.2015.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Complete Loss of Netrin-1 Results in Embryonic Lethality and Severe Axon Guidance Defects without Increased Neural Cell Death

Abstract: Netrin-1 regulates cell migration and adhesion during the development of the nervous system, vasculature, lung, pancreas, muscle, and mammary gland. It is also proposed to function as a dependence ligand that inhibits apoptosis; however, studies disagree regarding whether netrin-1 loss-of-function mice exhibit increased cell death. Furthermore, previously studied netrin-1 loss-of-function gene-trap mice express a netrin-1-β-galactosidase protein chimera with potential for toxic gain-of-function effects, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 28 publications
8
93
2
Order By: Relevance
“…The delay is less severe in Robo3 KOs than in Dcc KOs, consistent with previous observations in commissural axonal outgrowth [18]. Ntn1 KO, on the other hand, caused a more severe defect than Dcc KO, also consistent with previous observations in axon guidance [21, 25]. This is likely due to the fact that another homologue of DCC, the Neogenin (Neo1) receptor, has some redundant function and thus could compensate for the loss of DCC [24].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The delay is less severe in Robo3 KOs than in Dcc KOs, consistent with previous observations in commissural axonal outgrowth [18]. Ntn1 KO, on the other hand, caused a more severe defect than Dcc KO, also consistent with previous observations in axon guidance [21, 25]. This is likely due to the fact that another homologue of DCC, the Neogenin (Neo1) receptor, has some redundant function and thus could compensate for the loss of DCC [24].…”
Section: Resultssupporting
confidence: 91%
“…5). Ntn1 KOs were also reported to have a normal number of spinal cord neurons at E11.5 and E13.5 [21, 25]. Therefore, the loss of Ntn1 , Dcc, or Robo3 does not affect neurogenesis, either.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that TRIM9 was expressed in the hippocampus, although RNA probe and antibody specificity were not confirmed in Trim9 Ϫ/Ϫ samples (Li et al, 2001;Berti et al, 2002;Tanji et al, 2010). We reported the generation of a conditional Trim9 allele (Trim9 fl ) and germline deletion of murine Trim9 using CMV-Cre Trim9 Ϫ/Ϫ (Winkle et al, 2014).…”
Section: Trim9 Is Expressed In the Embryonic And Adult Murine Hippocamentioning
confidence: 99%
“…TRIM9 is an evolutionarily conserved member of the TRIpartite Motif (TRIM) family of ubiquitin ligases (Berti et al, 2002;Tanji et al, 2010). We recently identified TRIM9 as a regulator of neuronal morphogenesis in cortical neurons (Winkle et al, 2014;Menon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the generation of floxed mice [18] has allowed researchers to bypass this issue and expand novel roles for these cues at the cellular and tissue-specific level which will be further developed below.…”
Section: Introductionmentioning
confidence: 99%